Exploring Why Mothers Read: Motivational Goals for Shared Book Reading in Early Childhood (Open Society Conference, 2025)
This paper discusses the motivational orientation of mothers during shared book reading (SBR) with their toddler and their relationship with the educational backgrounds. The study is concerned with (1) the prevailing maternal intentions of the participation in SBR, as well as (2) the connection between the maternal intentions and the level of maternal education. A structured questionnaire was used to collect data on 32 mothers about the study aimed at evaluating the reason as to why they are interested in practicing SBR. In order to gather additional meaning and context to the quantitative results, six individuals were chosen to be interviewed on a follow-up basis through semi-structured interviews. The results of the descriptive analysis of the questionnaire revealed that, holistic motives of overall reinforcing emotional connections, enhancing speech formation, and activating cognition were dominant in all levels of education. Nonetheless, higher educated mothers had much lesser chances of expressing the teaching of skills motivation like teaching the alphabet or reading ability. These results show that the beliefs regarding SBR are predominantly holistic, but maternal education has an impact on the extent to which the instructional purposes are emphasized. Such understandings highlight the significance of providing the parents with complex insights into early literacy that will allow them to maximize both the language and emotional and cognitive development of children through effective interactions with literacy.